Abolitionism or reglamentarism? Contributions of Feminist Anthropology to the local debate on prostitution - Daich, Deborah (2012)
The issue of prostitution involves a series of debates over whether it should be regulated as sex work, prohibited and penalized, or abolished. Our country has, since 1936, an abolitionist position, which constitutes the hegemonic discourse on the debate about prostitution. Prostitution itself is problematic because it condenses several meanings and because it speaks of a vast and diverse sex market in which differences of class, ethnicity and gender come together in different combinations to give rise to countless scenarios. To recognize this diversity doesn’t imply ignoring the fact that differences assigned to men and women can be transformed, in each of these scenarios, in power differences and inequalities. Thus, in this paper, and based on a series of fieldwork experiences, I aim to reflect on the ways in which feminist anthropology can contribute to public debate on prostitution.